Class, caste and agrarian change: the making of farmers' protests. Issue 7 (10th November 2021) - Kumar, Satendra
ABSTRACT: Focusing on Jats of Western Uttar Pradesh (UP), North India, this commentary on India's farmers' protests provides an ethnographic and historical grounded picture of the larger political economic trends that have transformed everyday life and farmer identity in the region. It traces the rise and fall of the farmers identity popularized by Charan Singh and then the Bharatiya Kisan Union (BKU), its dissolution and replacement by Hindutva in the 2013, and its more recent return with the farmers protest. It explains why young Jats are re-embracing farmer identity even though they have no interest in working on the family farm, and why Jats have been able to build alliances with Dalits and Muslims.